STUDENTS’ PERCEPTION OF EXTENSIVE READING PROGRAM IN ENGLISH DEPARTMENT OF UNESA - Poetra, Arnanto Anggara (RETAIN, 2021)
These days, Extensive reading (henceforth ER) has become an alternative technique for teaching reading. ER requires learners to always read anywhere anytime since the purpose of ER is to enhance students’ reading skill. This case study, intended to look into students’ perception of the ER approach, used qualitative research design with four respondents from two different classes at English Language Education Study in State University of Surabaya. The data were gathered from the interview as the main source, observational notes and documents analysis as the confirmatory data to support the triangulation. Here, it is shown that ER increased students’ interests in reading, and built their awareness in reading either in or beyond class so that it became habitual for them to read more and upgrade their reading level, and as such, their perception of ER fits the characteristics of ER. In addition, it is recommended that the efficiency of ER should be bettered, and further studies are necessitated to analyze how lecturers can modify the class to make an output product from ER that can be used throughout generations, such as storybooks, dialog books etc.